Genomic activation of the EGFR and HER2-neu genes in a significant proportion of invasive epithelial ovarian cancers - Ghislain Vanessa; in 't Veld Peter; Xiangming Ji; Bourgain Claire; Teugels Erik; Vermeij Joanna; Neyns Bart; De Grève Jacques (BMC Cancer, 2008)
Abstract Background The status of the EGFR and HER2-neu genes has not been fully defined in ovarian cancer. An integrated analysis of both genes could help define the proportion of patients that would potentially benefit from targeted therapies. Methods We determined the tumour mutation status of the entire tyrosine kinase (TK) domain of the EGFR and HER2-neu genes in a cohort of 52 patients with invasive epithelial ovarian cancer as well as the gene copy number and protein expression of both genes in 31 of these patients by DGGE and direct sequecing, immunohistochemistry and Fluorescent in Situ Hybridisation (FISH). Results The EGFR was expressed in 59% of the cases, with a 2+/3+ staining intensity in 38%. HER2-neu expression was found in 35%, with a 2/3+ staining in 18%. No mutations were found in exons 18–24 of the TK domains of EGFR and HER2-neu. High polysomy of the EGFR gene was observed in 13% of the invasive epthelial cancers and amplification of the HER2-neu gene was found in 10% and correlated with a high expression level by immunohistochemistry. Mutations within the tyrosine kinase domain were not found in the entire TK domain of both genes, but have been found in very rare cases by others. Conclusion Genomic alteration of the HER2-neu and EGFR genes is frequent (25%) in ovarian cancer. EGFR/HER2-neu targeted therapies should be investigated prospectively and specifically in that subset of patients.